2017
DOI: 10.1016/j.jcms.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Is subcranial Le Fort III plus Le Fort I osteotomy stable?

Abstract: The purpose of this study was to test whether associated subcranial Le Fort III (sLF III) and Le Fort I (LF I) osteotomies are stable after large advancements of the middle third of the face and maxilla. The authors designed a retrospective study and enrolled a sample of consecutive patients with midface hypoplasia treated with associated sLF III and LF I osteotomies in this IRB-approved study between September 2013 and February 2015. To test whether the long-term stability was satisfactory, the authors compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
2
1
Order By: Relevance
“…As the muscles holding the maxilla are not yet stretched, a subsequent LF I osteotomy can be completed until the muscles and skin are stretched resulting in a net larger advancement that can be accomplished with a LF I advancement alone. 9 Contrary to this study, Schmitz et al, 21 demonstrated more vertical relapse than anteroposterior relapse measured at A point and central incisor tip at 1 year post surgery.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…As the muscles holding the maxilla are not yet stretched, a subsequent LF I osteotomy can be completed until the muscles and skin are stretched resulting in a net larger advancement that can be accomplished with a LF I advancement alone. 9 Contrary to this study, Schmitz et al, 21 demonstrated more vertical relapse than anteroposterior relapse measured at A point and central incisor tip at 1 year post surgery.…”
Section: Discussioncontrasting
confidence: 78%
“…They hypothesized that LF III/I advancement is more stable for larger horizontal movements compared with LF I alone because a LF III osteotomy will advance the pharyngeal and palatal muscles that insert to the maxilla. As the muscles holding the maxilla are not yet stretched, a subsequent LF I osteotomy can be completed until the muscles and skin are stretched resulting in a net larger advancement that can be accomplished with a LF I advancement alone 9. Contrary to this study, Schmitz et al,21 demonstrated more vertical relapse than anteroposterior relapse measured at A point and central incisor tip at 1 year post surgery.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation